HLA-DRB1*04 as a Risk Allele to Systemic Lupus Erythematosus and Lupus Nephritis in the Malay Population of Malaysia - Selvaraja, Malarvili; Chin, Voon Kin; Abdullah, Maha; Arip, Masita; Amin-Nordin, Syafinaz (Frontiers in Medicine, 2021)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease afflicting multiple organs. Lupus nephritis (LN) is a serious complication of SLE and remains a major cause of mortality and morbidity. Curative therapy remains unavailable as aetiology from genetic and environmental factors is still unclear. The present study was conducted to elucidate the link between HLA-DRB1 gene polymorphisms with SLE and LN through clinical and laboratory/biological presentations in a population of Malaysian Malay females with SLE. A total of 100 Malay female SLE patients inclusive of 70 SLE patients without LN and 30 patients with LN were included in this study. HLA-DRB1 alleles examination in SLE patients was performed using PCR-SSO and the alleles’ frequencies were compared with 951 publicly available datasets representing Malay healthy controls in Malaysia. Cytokines and free radical levels were detected by ELISA and bead-based multiplexed Luminex assays. The association between HLA-DRB1 alleles with clinical, serological manifestations and immune mediators were analysed using different statistical approaches whenever applicable. Our study showed that HLA-DRB1*0405, -*1201, -*1502, -*1602, were associated with the risk of SLE while HLA-DRB1*1201 allele was associated to a lower risk of SLE development. Furthermore, HLA-DRB1*04 showed significant association to lupus nephritis and arthritis whilst HLA-DRB1*15 was significantly associated with oral ulcer in Malay SLE patients. Association analysis of HLA-DRB1*04 with clinical and biological factors revealed that HLA-DRB1*04 was significantly associated with SLEDAI (Systemic Lupus Erythematosus Disease Activity Index) scores, anti-nuclear antibody (ANA), C-reactive protein (CRP) in the blood and total protein in the urine. SLE-carriers with HLA-DRB1*04 allele was significantly correlated to the increased levels of cytokines (IFN-y, GM-CSF, IL-17F, IL-18, IL-21 and VEGF) and were significantly showing negative correlation to IL-5 and free radicals (LPO and catalase enzyme) levels. The results suggested that disease severity in SLE may be determined by HLA-DRB1 alleles. The risk of HLA-DRB1*04 allele with lupus nephritis was supported by the demonstration of an intense inflammatory response in Malay SLE patients in Malaysia. More studies inclusive of a larger and multiple SLE cohorts are warranted in future to validate these findings.